Implementation of NN controlled DVR for Enhancing The Power Quality By Mitigating Harmonics - Abirami Periaswamy; Merin Lizbeth George (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Now a days there is a widespread use of  semiconductor devices, which are mostly implemented as the power switches for converters and inverters. These converters and inverters play a vital role in power systems both in transmission and distribution systems. This provides a way for the introduction of harmonics in the power system which leads to poor power quality. To overcome this many solutions have been suggested by the research community but each solution holds its own merits and demerits. Of all these suggested solutions, the Dynamic Voltage Restorer is one of the most cost effective systems for various power quality issues. In this paper the DVR is considered for enhancing the power quality by reducing the harmonics generated because of sensitive loads. Here the power quality is enhanced by controlling the DVR using Neural Network Controller which is trained by Levenberg Marquardt algorithm. In this paper the THD analysis of the voltage quantity is analysed by introducing an unbalanced three phase fault in the system. The simulation is done by using MATLAB/Simulink. From the results, it is verified that the harmonics are reduced by the NN controlled DVR unit. Also the simulation results are verified with the hardware results.